STUDI KASUS ASUHAN KEPERAWATAN GAWATDARURAT DENGAN DIAGNOSIS COMMUNITY ACQUIRED PNEUMONIA (CAP) DIRUANGAN INSTALASI GAWATDARURAT (IGD) ANAK RSUP DR. WAHIDIN SUDIROHUSODO MAKASSAR - Hartati Hartati; Muaningsih Muaningsih (Nursing Care Journal, 2024)
Introduction: Community-Acquired Pneumonia (CAP) is a lower respiratory tract infection that can affect children. Handling CAP requires comprehensive nursing care to minimize complications. This case study aims to evaluate the implementation of nursing care in two cases of CAP in the Children's Emergency Room at RSUP Dr. Wahidin Sudirohusodo Makassar. Method: used in this case study is a descriptive method, with case presentation and using a nursing process approach with a focus on one of the important problems in the selected case, namely nursing care for Community Acquired Pneumonia (CAP) clients. Results: Implementation of nursing care was carried out during the first 6 hours after entering the hospital. In An.L's case, evaluation showed that airway clearance was ineffective and the ineffective breathing pattern had not resolved. In the case of An.A, airway clearance is ineffective, breathing patterns are ineffective, and the risk of infection has not been resolved Analysis: The main inhibiting factors are limited implementation time and the patient's response to nursing interventions is not yet optimal.Conclusions and Suggestions: Evaluation shows that nursing problems have not been completely resolved in both cases. Suggestions to the hospital to provide regular education and training, especially regarding the latest service methods for patients with emergency nursing cases, to increase knowledge and skills for nursing staff, especially those in the pediatric emergency room at Dr. RSUP Hospital. Wahidin Sudirohusodo Makassar.